2005
DOI: 10.1021/tx050239z
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Formation of Interstrand Carbinolamine DNA Cross-Links by Crotonaldehyde- and Acetaldehyde-Derived α-CH3-γ-OH-1,N2-Propano-2‘-deoxyguanosine Adducts in the 5‘-CpG-3‘ Sequence

Abstract: The crotonaldehyde- and acetaldehyde-derived R- and S-alpha-CH3-gamma-OH-1,N2-propanodeoxyguanosine adducts were monitored in single-stranded and duplex oligodeoxynucleotides using NMR spectroscopy. In both instances, the cis and trans diastereomers of the alpha-CH3 and gamma-OH groups underwent slow exchange, with the trans diastereomers being favored. In single-stranded oligodeoxynucleotides, the aldehyde intermediates were not detected spectroscopically, but their presence was revealed through the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
100
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(115 citation statements)
references
References 54 publications
11
100
0
4
Order By: Relevance
“…64 These results were consistent with modeling of the native cross-links. 50 Lao and Hecht also concluded that the pyrimidopurinone cross-link arising from the 6R stereochemistry exhibited a more favorable orientation of the C6 CH 3 group. 20 Additional studies of the 6S diastereomer 12 were performed at pH 9.3.…”
Section: Synthesis Of Oligodeoxynucleotides Containing 1n 2 -Dg Enalmentioning
confidence: 98%
See 2 more Smart Citations
“…64 These results were consistent with modeling of the native cross-links. 50 Lao and Hecht also concluded that the pyrimidopurinone cross-link arising from the 6R stereochemistry exhibited a more favorable orientation of the C6 CH 3 group. 20 Additional studies of the 6S diastereomer 12 were performed at pH 9.3.…”
Section: Synthesis Of Oligodeoxynucleotides Containing 1n 2 -Dg Enalmentioning
confidence: 98%
“…A challenge was the preparation of stereochemically-defined amino diols for the crotonaldehyde (31,32) and 4-HNE adducts (33)(34)(35)(36) (Figure 2). [49][50][51][52] This strategy could not be applied to oligodeoxynucleotides containing α-OH-PdG (10), which were prepared using the modified phosphoramidite 25. 53,54 Interstrand Cross-linking by γ-OH-PdG…”
Section: Synthesis Of Oligodeoxynucleotides Containing 1n 2 -Dg Enalmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the formation of adduct 2 from acetaldehyde does not proceed through crotonaldehyde, but through N 2 -ethylidene-dGuo (3) (7). In duplex DNA, adduct 2 exits in equilibrium with its ring-opened aldehyde form (11) and can lead to the formation of interstrand cross-links and DNA-protein cross-links (7,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…have been characterized in reactions with DNA of other related compounds such as acrolein and malondialdehyde (7)(8)(9)(10).…”
mentioning
confidence: 99%